2021
DOI: 10.1177/10648046211028693
|View full text |Cite
|
Sign up to set email alerts
|

Human Factors Evaluation of Energy Visualization Dashboards

Abstract: Energy visualization systems provide information about use in real-time to assist users with energy efficiency. In this study, three energy visualization dashboards for small businesses were developed and tested. Performance measurement, NASA Task Load Index (TLX) workload assessment, and posttest survey were used to conduct the usability testing. Compared with the dashboards that were designed using line charts and tables, a dashboard designed using visuals (e.g., gauges, pie charts, and flashing lights) prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 11 publications
(13 reference statements)
0
2
0
Order By: Relevance
“…Although this approach already lowers the barrier for the integration of visualisations by manufacturing practitioners, there is still a challenge on deciding which visualisations are most appropriate for the application at hand; which ones can deliver the highest value for better decision making. Recent studies have shown how visualisations' "pre-attentive attributes" allow users to quickly identify differences in data without much cognitive processing [17]. Future work will include the development of pre-defined solutions made available through the solution configurator, providing the user with a selection of the most suitable visualisation components for a given application.…”
Section: Discussion and Future Workmentioning
confidence: 99%
“…Although this approach already lowers the barrier for the integration of visualisations by manufacturing practitioners, there is still a challenge on deciding which visualisations are most appropriate for the application at hand; which ones can deliver the highest value for better decision making. Recent studies have shown how visualisations' "pre-attentive attributes" allow users to quickly identify differences in data without much cognitive processing [17]. Future work will include the development of pre-defined solutions made available through the solution configurator, providing the user with a selection of the most suitable visualisation components for a given application.…”
Section: Discussion and Future Workmentioning
confidence: 99%
“…More than half of the tools (53%) present energy results in isolated and unrelated visualizations, while the other half (47%) have designed a dashboard-like interface that allows for exploring data in an organized way, contextualizing the information and hierarchizing graphics. In the latter case, the interface allows the user to interact with the information [44][45][46][47][48][49][50], choose parameters [10,33,[51][52][53][54][55][56][57], and analyze the context through 3D visualizations [10,[50][51][52][56][57][58] or floor plans of the building [10,44,53,56,58]. It is also noted that the dynamic capacity of data visualization is an underutilized feature in the tools.…”
Section: Scientific Literaturementioning
confidence: 99%
“…Regarding the third LOD of data analysis, 40% of the tools allow the user to delve into the specific value and, through interactions such as clicks, identify the variables that influence the metrics according to time periods [2,53,59,60]. Moreover, they allow the association of these variables with consumption ranges [1,55,59,61], presenting data divided by zones or environments [33,53,58] and parameters or categories [44][45][46]49]. Likewise, at this same level, it is possible to compare metrics to a performance time-scale [47,48,51,55,59,61,62], showing values by seasons, months, days, hours, and sub-hours.…”
Section: Scientific Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…In the power plants, neglecting PSFs, including human factors, and sustainable integration with workplace energy management performance EMP resulted in an evident weakness in the energy management performance of power plants. Therefore, the integration between CSFs of PSFs and CSFs of EMP remains a research gap and an urgent problem that needs to be solved according to previous studies [3,4]. Poor performance in the industrial sector, especially in the electricity sector, negatively affects the power plant and contributes to the increase in human errors and the weakness of human factors [5].…”
Section: Introductionmentioning
confidence: 99%